Evolution and Modern Solutions in Managing Sales Competitiveness Based on Trade Calculation - Vladimir A. CHERNOV (Communications of International Proceedings, 2020)
The main competitive advantage of the world economy at the present stage is the ability to reduce costs in the competitive struggle of the world market participants. For the most accurate cost management, calculation is necessary, which, according to the hypothesis of the study, is the main means of effective, competitive management of trade processes, sustainable innovative development of the sphere of commodity circulation. In the coming digital economy of the information society, calculation methods are becoming an important intellectual asset as a means of designing information for decision-making by artificial intelligence in cloud services. Calculation is a necessary condition for the introduction of new technologies of "lean production". These methods of controlling allow the most rational, complete and effective management of costs, prices, product range, financial results and competitiveness in the sphere of circulation and serve as an algorithm for neural networks in creating digital economy technologies. The present article dwells on the questions of profit management on the basis of trade calculation. It gives the historical overview of development of calculation methods and their application in the most acute issue of regulation of sales competitiveness. The article shows out that issue of distribution chain is treated in the fullest way in Russian sources.
Keywords: Calculation; competitiveness; action; distribution cost; cost capacity; income capacity; commodity groups accounting.